(3OQ GdSMGHI aj HjGf hajGJ GdUMGHIs - (3GdQVj GdUGZGfj , GdMSf Hf eMeO Hf GdMSf Hf MjOQ, QVj GdOjf,J (B650 (3g` s ((3eMeO Hf eMeO hjOYi YHO GdQMje Hf jYbhH Hf eMeO Hf EHQGgje GdajQhRGHGOi s)
(3ChdgG (B:s
(3GdMeO ddg GdefTi GdeHjO GdeYjO gPG cJGH LeYJ ajg Hjf GdeNJUQ GdPi cfJ CdaJg ai HjGf ehGVY hajGJ GdUMGHg QVi Gddg Yfge hHjf Pjdg GdPi PjdJ Ydjg dJJe GdaGFOg s
(3eQJH Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B279s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B361 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B145 s
Keywords: (3GdJGQjNs